Recent Advances in Mechanochromism of Metal-Organic Compounds - Wang, Xiao-Yan; Lv, Liqiang; Sun, Li; Hou, Yue; Hou, Zhenghao; Chen, Zhao (Frontiers in Chemistry, 2022)
Smart luminescent materials, which can respond to the changing of external environment (light, electricity, force, temperature, etc.), have always been one of the research hotspots. Mechanochromism refers to the materials whose emission color or intensity can be altered under the stimulation of external mechanical force. This kind of smart materials have been widely used in data storage, information encryption and sensors due to its simple operation, obvious and rapid response. The introduction of metal atoms in metal-organic compounds brings about fascinating metalophilic interactions and results in more interesting and surprising mechanochromic behaviors. In this mini-review, recent advances in mechanochromism of metal-organic compounds, including mono-, di-, multinuclear metal-organic complexes and metallic clusters are summarized. Varies mechanisms are discussed and some design strategies for metal-organic compounds with mechanochromism are also presented.